Causals, Concessives, and the Scope of Negation - Fretheim, Thorstein (Kalbotyra, 2003)
While wide-scope negation of a causal relation between two propositions P and Q – as in the English sentence I didn’t move because the rent was raised – is truth-conditionally underdetermined as to whether the speaker did or did not move and the rent was or was not raised, use of a concessive construction – I didn’t move although the rent was raised – eliminates the inherent vagueness of the negative causal construction, as it encodes the information that the rent was raised but that the speaker did not move because of/in spite of that. The intuitively felt resemblance between the causal truth-conditionally underdetermined construction and the concessive construction is claimed to have caused an Old Norse causal connective to be re-analysed as a non-truth-conditional concessive, for det (‘for that’), in modern Norwegian. For det is referred to as a ‘weak’ concessive with a procedural meaning in the sense of relevance theory, a meaning which will be pragmatically strengthened to a regular ‘strong’ concessive expressing the expectation that Q is false if P is true, in case considerations of relevance support the inferred ‘strong’ interpretation of the token in context.